2008
DOI: 10.1093/annonc/mdm465
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in FIGO stage IB–IIA small cell neuroendocrine carcinoma of the uterine cervix treated surgically: results of a multi-center retrospective Korean study

Abstract: Results: Of the 68 patients, 43 had FIGO stage IB1 SCNEC, 15 had stage IB2, and 10 had stage IIA. Seven were treated with radical surgery alone; 11 with neoadjuvant chemotherapy (NACT) followed by radical surgery; 24 with radical surgery followed by adjuvant chemotherapy; and 26 with radical surgery followed by adjuvant radiation or chemoradiation. After a median follow-up of 44 months (range, 6-113 months), the 2-year and 5-year survival rates for all patients were 64.6% and 46.6%, respectively. Univariate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
110
9
10

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(137 citation statements)
references
References 22 publications
8
110
9
10
Order By: Relevance
“…Notably, all five patients with early stage SCCC including two cases with bulky tumors had no pelvic recurrence, a median survival of 47.4 months and an OS rate at five years of 80%. Although limited by the small number of patients included in this analysis, we did show improvement in the overall survival rate over the previously reported five-year survival of 31.6-46.6% for stage I-IIA patients (Chan et al 2003;Lee et al 2008;Cohen et al 2010). In addition, Cohen et al reported that radical hysterectomy was an independent prognostic factor for survival in a multivariate analysis of 188 patients with SCCC (Cohen et al 2010).…”
Section: Discussioncontrasting
confidence: 40%
“…Notably, all five patients with early stage SCCC including two cases with bulky tumors had no pelvic recurrence, a median survival of 47.4 months and an OS rate at five years of 80%. Although limited by the small number of patients included in this analysis, we did show improvement in the overall survival rate over the previously reported five-year survival of 31.6-46.6% for stage I-IIA patients (Chan et al 2003;Lee et al 2008;Cohen et al 2010). In addition, Cohen et al reported that radical hysterectomy was an independent prognostic factor for survival in a multivariate analysis of 188 patients with SCCC (Cohen et al 2010).…”
Section: Discussioncontrasting
confidence: 40%
“…In cases of early-stage, the rates of LVSI, DSI, pelvic lymph node metastasis and parametrial invasion were high as 60%, 46%, 37% and 13%, respectively (Lee et al, 2008). Although, they have no data of ovarian metastasis in this cell type, certainly, the tendency of metastatic characteristic and the rate of ovarian metastasis were higher.…”
Section: Discussionmentioning
confidence: 93%
“…Neuroendocrine cervical carcinoma is the most aggressive cell type, high potential of metastasis, and poor prognosis (Lee et al, 2008;Cohen et al, 2010;Wang et al, 2012). In cases of early-stage, the rates of LVSI, DSI, pelvic lymph node metastasis and parametrial invasion were high as 60%, 46%, 37% and 13%, respectively (Lee et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the lack of data, most clinicians favor the use of combined chemotherapy and RT because of the strong evidence supporting concurrent chemoradiotherapy in other subtypes of cervical cancer. Adjuvant chemotherapy alone could be considered an option in patients who have undergone radical hysterectomy [11]. The role of surgery for large cell neuroendocrine carcinoma is not well studied.…”
Section: Discussionmentioning
confidence: 99%